FEATURES OF THE EXCIPIENTS SELECTION FOR SEMI-SOLID DOSAGE FORMS - Shostak, T. A.; Bilous, S. B.; Gudz’, N. I.; Kalynyuk, T. G. (Фармацевтичний часопис, 2015)
The requirements for the selection of excipients during the pharmaceutical development of semi-solid medicinal preparations for cutaneous application were generalized from a point of view of their impact on the quality, efficacy and safety of medicinal preparations. It was justified which excipients from the examined groups should be used for the pharmaceutical development of ointments, gels, and creams. The information about physico-chemical and technological properties of excipients and their compatibility was summarized.